2022
DOI: 10.3390/s22197623
|View full text |Cite
|
Sign up to set email alerts
|

EEG/fNIRS Based Workload Classification Using Functional Brain Connectivity and Machine Learning

Abstract: There is high demand for techniques to estimate human mental workload during some activities for productivity enhancement or accident prevention. Most studies focus on a single physiological sensing modality and use univariate methods to analyse multi-channel electroencephalography (EEG) data. This paper proposes a new framework that relies on the features of hybrid EEG–functional near-infrared spectroscopy (EEG–fNIRS), supported by machine-learning features to deal with multi-level mental workload classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Our analysis showed that connections have a significant correlation with the prefrontal brain regions, distributed mostly between the frontal and other regions of the brain. A similar result has been reported by Shen et al [ 4 ] and Song et al [ 46 ]. Research has shown that people with generalized anxiety disorder (GAD) may have abnormal FC [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our analysis showed that connections have a significant correlation with the prefrontal brain regions, distributed mostly between the frontal and other regions of the brain. A similar result has been reported by Shen et al [ 4 ] and Song et al [ 46 ]. Research has shown that people with generalized anxiety disorder (GAD) may have abnormal FC [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 91%
“…To the best of our knowledge, it is worth mentioning, our experimental results provide the first causal analysisbased explanation for the significant differences in EEG-fNIRS coupling between the 0-back condition and the 2back and 3-back conditions, while no significant differences were observed between the 2-back and 3-back conditions. This viewpoint has been partially reflected in previous WM classification studies based on EEG-fNIRS [54]. However, it does not explain the underlying reasons for this phenomenon.…”
Section: Discussionmentioning
confidence: 84%
“…All subject-wise regions of interest (ROI) time-series were averaged within each ROI and preprocessed into subject-wise, ROI-to-ROI adjacency matrices, which has been proven to be successful in previous studies [49] , [50] , [51] , [52] , [53] , [54] , calculated as Pearson’s correlation coefficient for each possible pair of the 246 ROIs. This approach generates a database with 30135 columns and more than a thousand rows ( )., which constituted our final dataset to be used for classification.…”
Section: Experimental Data and Setupmentioning
confidence: 99%